Reliability performances of low voltage & medium voltage networks in different areas - Mohd Ikhwan, Muhammad Ridzuan (Institute of Electrical and Electronics Engineers Inc., 2020)
Distribution network consists of low voltage (LV) and medium voltage (MV) networks. Each year, most distribution network operators (DNOs) report their network performance without separating LV and MV network performance, and also without separating urban and rural network performance. Since there is no separation of area and voltage level performances, there is no indicator that urban network is better than sub-urban and rural areas networks. In order to find the performance of distribution network, analytical method is applied to all types of networks; LV urban, LV sub-urban, LV rural, MV urban, MV sub-urban and MV rural networks. Analytical method involves mathematical solution to evaluate the reliability performance. It usually focuses only on mean value. The aim of this paper is to examine the performance of LV and MV networks in urban, sub- urban and rural areas. It is expected that urban network performance is better than sub-urban and rural networks, whether in LV and MV networks. Based on the result, certain network performance were not as expected due to several reasons; network configuration, values of mean fault rates and repair times, and number of components.